How Artificial Intelligence Can Be Integrated into Journalistic Practices - Enes Baloğlu; Emrah Budak (Vivat Academia)
Introduction: Technological developments are constantly transforming many sectors. Artificial intelligence technologies are also leading to changes and transformations in journalistic practices. As AI technologies have made significant advances in the last few years, there is a growing need for journalism students to familiarize themselves with different AI technologies and adapt to such changes. Methodology: Semi-structured interviews were conducted with industry representatives and academics on which courses should be added in higher education in the process of using AI in journalism practices. Course proposals were developed from the main themes that emerged.  Results: At the same time, workers in the media sector need to adopt AI technologies to adapt to communication technologies. Based on the results of interviews with industry experts and journalism academics and a literature analysis, this paper suggests that the curriculum of journalism departments should include courses on AI topics and applications. In this sense, it seems inevitable that both the representatives of the media sector and those preparing for the sector should be trained in artificial intelligence. Conclusion: The main conclusion of the study is that rather than artificial intelligence replacing human journalists, press sector employees and journalism students will increase productivity with artificial intelligence by receiving the necessary training.